Asset Valuation and Income Theory. - Lemke, Kenneth W. (The Accounting Review, 1966)
The article focuses on the issue of revolutionizing accounting theory, which has been a left out proposal in the past few years. Revolutionaries have devoted a high proportion of their total effort to the related problems of profit determination and asset valuation. C.T. Horngren, a scholar, suggested a compromise plan which attempts to accommodate clashing interpretations of the significance of realization only. Horngren's article attempts, through a critical examination of some important proposals of recent years, to discover the root cause of disagreement over the optimum concept of value and to suggest a compromise path along which the revolution in valuation and income theory may progress. The article concludes that a compromise solution to this conflict of widely divergent views in this area would be to adopt a valuation rule that requires each asset to be valued according to the basis offering "sufficiently definite verifiable evidence" and yielding what is believed to be the closest approximation to the present value of the asset's future cash flows.